OPTIMIZING THE DIAGNOSIS AND TREATMENT OF DUANE SYNDROME (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Duane syndrome is a rare anomaly in the development of the extraocular muscles, manifested by limited mobility of the eyeball, especially to the sides, and accompanied by various visual impairments [5, 9]. This pathology is of great importance in ophthalmology, as it can significantly reduce the quality of life of patients, including due to the development of strabismus [3, 7] and retraction of the eyeball [1, 2, 6, 8]. In Uzbekistan, data on the prevalence and clinical characteristics of Duane syndrome remain insufficient [4]. Therefore, improving diagnostic and treatment methods for this syndrome is an urgent task for medical practice